EVALUASI PEMBELAJARAN PAI TERHADAP KUALITAS HASIL BELAJAR PESERTA DIDIK DI SMP MUHAMMADIYAH 5 LEKOK - Sinta Ma’sumah; M Jadid Khadavi (Al-Kindi, 2025)
This study aims to evaluate the Islamic Religious Education (PAI) learning process in relation to the quality of student learning outcomes at SMP Muhammadiyah 5 Lekok. Learning evaluation is a crucial aspect of the educational process, as it helps measure the effectiveness of methods, strategies, and approaches used by teachers in delivering the material. This research employs a qualitative approach using observation, interviews, and documentation techniques. The subjects of the study include PAI teachers, students, and the school principal. The results indicate that the evaluation of PAI learning has been systematically implemented through cognitive, affective, and psychomotor assessments. However, challenges remain in utilizing evaluation results to improve the learning process. The quality of student learning outcomes is generally good but not evenly distributed across all classes. Factors influencing the quality of learning outcomes include teacher competence, student motivation, and support from the school environment and families. Therefore, it is necessary to enhance teacher capacity in developing comprehensive evaluation instruments and utilizing technology in the evaluation process. Well-planned and continuous evaluations are believed to improve the quality of PAI learning and overall student outcomes.